Faktor-Faktor yang Mempengaruhi Agresivitas Remaja - Putri Rahmaning Sekar (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
Aggressiveness is the desire to hurt other individuals, by expressing negative feelings such as hostility to achieve the desired goal. The aggressiveness component consists of physical aggression, verbal aggression, anger, and hostility. The purpose of this study is to identify the factors that influence aggressiveness. Literature searches were carried out on the Researchgate, Scopus, Springer, and Google Schoolar electronic databases using the keywords